The Role of Entrepreneurial Marketing and Relationship Marketing That Strengthen The Women Entrepreneurs' Business Performance - Shiratina, Aldina; Ramli, Yanto; Imaningsih, Erna Sofriana; Rajak, Adnan; Ali, Anees Janee (Indonesian Journal of Business and Entrepreneurship, 2023)
The role of marketing in small and medium-sized enterprises (SMEs) has a unique characteristic compared to conventional marketing in large organizations. This research is focused on the apparel industrial entrepreneurs in the city of Bandung. This research intended to examine the impact of entrepreneurial and relationship marketing on business performance, moderated by motivation. The research method used in this paper was the quantitative method with descriptive and verificative approaches. The sample size used in this research is around 150 SME businesses. This research indicates that business motivation significantly moderated the impact of entrepreneurial marketing on business performance and significantly moderated the effect of relationship marketing on business performance. This research concluded that it is crucial for SME entrepreneurs in the fashion sector in Bandung to further develop their businesses by motivating them to improve their business performance through entrepreneurial marketing and relationship marketing. Keywords: entrepreneurial marketing, relationship marketing, business performance, motivation, SMEs